An Analysis of Teachers Technique in Teaching Listening to Students of SMP Negeri 1 Limboto - Yenrika H. Nune; Elsje L. Sambouw; Farid Muhamad (Transbahasa, 2022)
This research aimed to know what are the techniques that use by teachers in teaching listening to students of SMP Negeri 1 Limboto. According to (Harmer: 2007) there are many techniques that teacher uses in teaching listening, every teacher has a technique in teaching listening. There were seven techniques that can use in teaching listening, those were fill in the gap, guessing pictures, finding mistakes, rearranging sentences or paragraph, matching, English song and dictation. Based on this theory, the researcher had formulated the questionnaire and the interview. It is a qualitative research where in analyzing the data the researcher used interview and gave them questionnaire which the procedure explained that the process of analysis involve preparing, the data for analysis, identify the data, deeper understanding the data representing the data the last making interpretation the data. The result of the research found that the teacher at the SMPN 1 Limboto did implement some teaching techniques in teaching listening. Those techniques were fill in the gap, guessing pictures, finding mistakes, rearranging words or paragraph, matching, English song and dictation and the most frequently used technique was fill in the gap. Fill in the gap had found most frequently since it can be used to test a variety of areas such as vocabulary, grammar and were very effective at testing listening for specific words. Moreover, the researcher found that teacher A applied the fill in the gap, 2 finding mistakes, rearranging sentences or paragraph, matching, English song and dictation. Teacher C as in other hand also applied the fill in the gap, finding mistakes, rearranging sentences or paragraph, English song and dictation but did not apply the matching technique. While for the teacher B only applied fill in the gap technique and English song technique. Therefore all the techniques stated by Harmer was used by the teachers in teaching listening.